Diseño de un plan de marketing relacional (Cstomer Relationship Management) CRM para la empresa Alconlab Ecuador S.A. dedicada a la importación y comercialización de medicamentos, insumos y equipos oftalmológicos ubicada en el sector la carolina del distrito metropolitano de Quito. - Navas Tamayo, Cintya Eliana (2014)
The present research work deals with the design of a relational marketing plan for the company ALCONLAB ECUADOR SA dedicated to the importation of drugs, supplies and ophthalmic equipment. For this purpose it was necessary to analyze the current situation of the company to initiate a process of design and implementation of the CRM model (Customer Relationship Management), according to the needs and capabilities empresa.El first chapter presents the problem and describe all the conditions of the problem and its systematization.